The use of cryopreserved sea urchin embryos (Paracentrotus lividus) in marine quality assessment. (June 2015) - Paredes, E.; Bellas, J.
Highlights: We establish a cryopreserved sea urchin embryo bioassay and provide comparison to the standardized bioassay. We calculated the EC50 s for two metals (copper and lead) and 2 organic compounds (4-MBC and PB-3). We obtained a slope of 0.69 comparing the cryopreserved blastula and standard bioassay. The cryopreserved blastula bioassay produces more sensitive results. Abstract: We have established for first time an ecotoxicological bioassay using cryopreserved sea urchin embryos ( Paracentotus lividus ) and provided a comparison to the already standardized sea urchin embryo–larval bioassay, using selected (organic and inorganic) pollutants and sediment elutriates from 4 different locations from Ria de Vigo harbour (Galicia, NW Iberian Peninsula). A cryopreservation protocol was designed in order to enable the successful cryopreservation and cryobanking of gametes and embryos to be used for marine quality assessment and ensure the accessibility to high quality reproductive material all year round, as an option to conditioning adults for out of season reproduction. The calculated EC50 using the cryopreserved blastula was 53.7 μg L − 1 for copper, 81.0 μg L − 1 for lead, 300.6 μg L − 1 for BP-3 and 300.6 μg L − 1 for 4-MBC. The sensitivity of the classic sea urchin embryo–larval bioassay was compared with the bioassay conducted with cryopreserved blastula. The results showed that the use of cryopreserved blastula bioassay allows detecting lower concentrations of pollutants in comparison with the classic bioassay.